2005
DOI: 10.1124/dmd.105.005397
|View full text |Cite
|
Sign up to set email alerts
|

TRANSCRIPTIONAL REGULATION OF THE NAD(P)H:QUINONE OXIDOREDUCTASE 1 AND GLUTATHIONES-TRANSFERASE YA GENES BY MERCURY, LEAD, AND COPPER

Abstract: ABSTRACT:Recently, we demonstrated the ability of heavy metals, particularly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…This response is not unique to ethanol-exposed embryos. Similar effects have been observed in cells treated with a numbers of other toxic chemicals, including heavy metals (19,23), cigarette smoke (22), and arachidonic acid (17). Of particular interest to this study is that an increase in Nrf2 protein has also been observed in livers and hepatocytes of alcohol-fed mice and rats (16).…”
Section: Discussionsupporting
confidence: 59%
“…This response is not unique to ethanol-exposed embryos. Similar effects have been observed in cells treated with a numbers of other toxic chemicals, including heavy metals (19,23), cigarette smoke (22), and arachidonic acid (17). Of particular interest to this study is that an increase in Nrf2 protein has also been observed in livers and hepatocytes of alcohol-fed mice and rats (16).…”
Section: Discussionsupporting
confidence: 59%
“…Recent studies from our laboratory showed that mercury (Hg 2+ ), lead (Pb 2+ ), and copper (Cu 2+ ) modulate the expression of Nqo1 gene in Hepa 1c1c7 cells through AhR/XRE-and Nrf2/ARE-dependent mechanisms [20,21]. In addition, we recently showed that all the three metals were able to induce the NF-κB and AP-1 binding activity in Hepa 1c1c7 cells [22].…”
Section: Introductionmentioning
confidence: 96%
“…Heavy Metal Toxicity: In vitro exposure of mouse hepatoma cells to heavy metals including inorganic mercury and lead results in the transcriptional activation of Nqo1 and Gst genes (Korashy and El-Kadi, 2006). Similarly, arsenic induces Nqo1 in hepatoma cells by stabilizing Nrf2 protein (He et al, 2006).…”
Section: Cytochrome P450 2e1-associated Oxidative Stressmentioning
confidence: 99%